2009
DOI: 10.2165/11315680-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors

Abstract: Histone deacetylase (HDAC) inhibitors are a new group of anticancer agents that have a potential role in the regulation of gene expression, induction of cell death, apoptosis and cell cycle arrest of cancer cells by altering the acetylation status of chromatin and other non-histone proteins. In clinical trials, HDAC inhibitors have demonstrated promising antitumour activity as monotherapy in cutaneous T-cell lymphoma and other haematological malignancies. In solid tumours, several HDAC inhibitors have been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(77 citation statements)
references
References 150 publications
0
77
0
Order By: Relevance
“…Some studies have shown that the decrease in HDAC activity is associated with the suppression of tumor cell growth [55,56]. In a variety of tumors, the change to a greater state of acetylation, as a result of HDAC inhibition, can result in modification of the expression of several genes.…”
Section: Butyrate In Epigenetic and Gene Expressionmentioning
confidence: 99%
“…Some studies have shown that the decrease in HDAC activity is associated with the suppression of tumor cell growth [55,56]. In a variety of tumors, the change to a greater state of acetylation, as a result of HDAC inhibition, can result in modification of the expression of several genes.…”
Section: Butyrate In Epigenetic and Gene Expressionmentioning
confidence: 99%
“…HDAC2 is a regulator of chromatin compaction status and its down-regulation or inhibition causes chromatin decondensation and sensitization to DNA targeted anti-cancer drugs (19). Class II HDACs have more tissue specific regulatory functions (Table 1) (4, 8, 14). HDAC1 knock-out is an embryonic lethal by day 9.5 and results in proliferation defects of embryonic stem cells (20).…”
Section: Histone Deacetylases (Hdacs)mentioning
confidence: 99%
“…A number of recent papers have reviewed the current status of clinical trials with HDAC inhibitors as monotherapy and combination for cancers (4, 8-12). …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] HDAC inhibitors (HDACi) exert a wide range of anticancer effects including induction of cell cycle arrest, promotion of apoptosis (extrinsic and intrinsic), inhibition of DNA damage repair, blockage of angiogenesis, and inhibition of metastasis. 1,6 Their mechanism of action, resulting from the modulation of gene and protein function, affects cellular processes that form the basis of cancer cell malfunctioning and presumably can also affect the activity of conventional drugs, rendering them ideal candidates for combination strategies. Indeed, there are a growing number of reports on the additive or synergistic effects when HDACi are combined with other cytotoxic or targeted therapeutics including several preclinical studies.…”
Section: B S T R a C Tmentioning
confidence: 99%